If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-b-9=-3+8+b
We move all terms to the left:
-b-9-(-3+8+b)=0
We add all the numbers together, and all the variables
-b-(b+5)-9=0
We add all the numbers together, and all the variables
-1b-(b+5)-9=0
We get rid of parentheses
-1b-b-5-9=0
We add all the numbers together, and all the variables
-2b-14=0
We move all terms containing b to the left, all other terms to the right
-2b=14
b=14/-2
b=-7
| 5/6x+2=3/8 | | 8-a=3+2(a-5) | | 2.3=5.5y | | ((x-1)x)/2+x=1485 | | 8a=32.8 | | -5x+5=7x-15 | | 32=-3(4d+7) | | 2.3y=82.5 | | 72=82-y | | 4w^2+3w=46 | | 7x+2=3x−7 | | 4(-1)+4y=24 | | 14+3y=12 | | 1.8x=-5.94 | | a/4=52 | | a/9+2=4 | | 3=a+(a-2) | | x/1.5+3.4=1.3 | | 1/x+1+5=8 | | 8w-1=3(w+1)+1 | | 30+3y=6 | | 5s-9-8s=25 | | x/15+3.4=1.3 | | 5^x=66 | | 6x-15=5-4x | | 45+5y=15 | | 9(s+1)=18 | | -3x+1/2=5 | | 4w+6=6 | | 8x+18=-x | | 4n+6=(5n+3) | | y/6+y/3=8/5 |